NOTA PREVIA SOBRE EL TRATAMIENTO DE LA NEUMOENCEFALITIS DE LAS AYES (NEWCASTLE) CON ANTITOXINA TETANICA - MOLERES RUIZ, RODOLFO (Fed Departamento Health, CD MEXICO, DF, MEX, 1948)
There is some similarity between the action of the neurotropic virus of the Newcastle disease and that of the tetanus toxin The neutralization of the Newcastle virus by tetanus antitoxin was demonstrated by in vitro neutralization of the virus by the ant
CIENC MEX
Keywords: NOTA, TRATAMIENTO, NEUMOENCEFALITIS, AYES, ANTITOXINA, TETANICA; MULTIDISCIPLINARIA; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); VIROLOGIA MEDICA